USE OF GABIONS IN LANDSCAPING AND ARCHITECTURAL ART DECORATION OF HIGHWAYS AND CITY STREETS - Ubaydullayev Farkhod Bakhtiyarullaevich; Ergashev Khahramon Khushvaktovich (Journals Park Publishing, 2024)
In landscape architecture, the size, shape and material of gabions are determined by the area of the landscaped area. Gabions can be used not only for landscaping, but also for erosion protection. Gabions are used not only to decorate the site being landscaped, but also protect river beds from erosion, strengthen slopes and prevent soil erosion. Additional ornamental plants can act as small architectural forms from gabion structures, the stems and leaves of which encircle the lattice of the structure and combine beautifully with the stone. For plant roots, forms can be provided in the form of a gabion structure filled with fertile soil.
Keywords: Landscape, design, architecture, decorativeness, flowers, gabions, size, shape, materials, choice, landscaping, small architectural forms, use, decoration, flower beds, composition, urban, attractive appearance, easy installation, cleanliness of materials.